Experimental Study on Surface Polishing of SLM-316L Stainless Steel via Laser Treatment and Mechanical Grinding - Wei Fang; Qiuling Wen; Jiaxin Hu; Feng Jiang; Zhongwei Hu; Xian Wu; Jinlin Yang; Xiaoguang Wang (Micromachines)
The 316L stainless steel material boasts exceptional corrosion resistance and plasticity, among other benefits, and finds extensive application in automotive components, molds, aerospace parts, biomedical equipment, and more. This work focuses on the surface polishing of selective laser melting (SLM) 316L stainless steel using 1064 nm nanosecond laser processing and mechanical grinding. The influence of laser processing parameters on the surface roughness of SLM-316L stainless steel was investigated using an orthogonal experiment. After laser processing, the surface roughness of SLM-316L stainless steel was reduced from 7.912 μm to 1.936 μm, but many randomly distributed irregular micro-cracks appeared on the surface. EDS and XRD detections illustrated that iron oxides were generated on the surface of SLM-316L stainless steel after laser processing. Mechanical grinding was further performed to achieve a nanometer surface finish and remove the metal oxides and micro-cracks generated on the surface of SLM-316L stainless steel after laser processing. The AFM measurement results indicate that the surface roughness of SLM-316L stainless steel was reduced to approximately 3 nm after mechanical grinding. Moreover, the micro-cracks and iron oxides on the surface of laser-processed SLM-316L stainless steel were completely removed. This work provides guidance for the precision polishing of SLM-316L stainless steel.